Risky Bodies in the Plasma Bioeconomy: A Feminist Analysis. (March 2015) - Kent, Julie; Farrell, Anne-Maree
In 2003 the UK National Blood Service introduced a policy of 'male donor preference' which involved women's plasma being discarded following blood collection. The policy was based on the view that data relating to the incidence of Transfusion-Related Acute Lung Injury (TRALI) was linked to transfusion with women's plasma. While appearing to treat female donors as equal to male donors, exclusion criteria operate after donation at the stage of processing blood, thus perpetuating myths of universality even though only certain 'extractions' from women are retained for use in transfusion. Many women in the UK receive a plasma-derived product called Anti-D immunoglobulin which is manufactured from pooled male plasma. This article examines ways in which gender has significance for understanding blood relations, and how the blood economy is gendered. In our study of relations between blood donors and recipients, we explore how gendered bodies are produced through the discursive and material practices within blood services. We examine both how donation policies and the manufacturing and use of blood products produces gendered blood relations.